HUBUNGAN INTERAKSI SOSIAL DAN PERKEMBANGAN BAHASA EKSPRESIF ANAK UMUR EMPAT SAMPAI ENAM TAHUN DI TK DESA PONDOK SUKOHARJO - Nastiti, Euis Egidea; Anisyah Dewi Syah Fitri (Tahta Media Group, 2023)
Background: Khotimah (2016) social interaction is a dynamic social relationship that includes relationships between individuals, between human groups, as well as between individuals and human groups. In interaction requires language to communicate. Language is the main communication tool used in everyday life. Language is also used to express everything that is on the mind so that other people can understand it. According to (Saputri 2016) expressive language is a child's way of expressing feelings, words, expressions, intonation, movements, and desires in a simple but meaningful way to others around them. Purpose: This study aims to determine whether there is a correlatio of social interaction and expressive language development in kindergarten Desa Pondok Sukoharjo. Methods: The research design used descriptive correlative with type. The sampling technique used was total sampling. The sample size in this study was 27 samples. The statistical test used in this study was the Spearman's rho test. Research Results: The results of Spearman's rho test showed that the Sig. 0.028 which means Sig value <0.05 with the Correlation Coefficient / r value of 0.422. So that the alternative hypothesis (Ha) is accepted, namely that there is a relationship between social interaction and expressive language skills, with moderate accuracy. Conclusion: There is a correlation between social interaction and the development of expressive language for children age four until six years in Kindergarten Desa Pondok Sukoharjo